Advertisement Remove all ads

Factorise the Given Expressions −4asquare2 + 4ab − 4 Ca - Mathematics

Factorise the given expressions  −4a2 + 4ab − 4 ca

Advertisement Remove all ads

Solution

4a2 = 2 × 2 × a × a

4ab = 2 × 2 × a × b

4ca = 2 × 2 × c × a

The common factors are 2, 2, and a.

∴ −4a2 + 4ab − 4ca = − (2 × 2 × a × a) + (2 × 2 × a × b) − (2 × 2 × c × a)

= 2 × 2 × a [− (a) + b − c]

= 4a (−a + b − c)

  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

NCERT Class 8 Maths Textbook
Chapter 14 Factorisation
Exercise 14.1 | Q 2.08 | Page 220
Advertisement Remove all ads

Video TutorialsVIEW ALL [1]

Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×